Varying conjunctival immune response adaptations of house finch populations to a rapidly evolving bacterial pathogen - Kuttiyarthu Veetil, Nithya; Henschen, Amberleigh E.; Hawley, Dana M.; Melepat, Balraj; Dalloul, Rami A.; Beneš, Vladimír; Adelman, James S.; Vinkler, Michal (Frontiers in Immunology, 2024)
Pathogen adaptations during host-pathogen co-evolution can cause the host balance between immunity and immunopathology to rapidly shift. However, little is known in natural disease systems about the immunological pathways optimised through the trade-off between immunity and self-damage. The evolutionary interaction between the conjunctival bacterial infection Mycoplasma gallisepticum (MG) and its avian host, the house finch (Haemorhous mexicanus), can provide insights into such adaptations in immune regulation. Here we use experimental infections to reveal immune variation in conjunctival tissue for house finches captured from four distinct populations differing in the length of their coevolutionary histories with MG and their disease tolerance (defined as disease severity per pathogen load) in controlled infection studies. To differentiate contributions of host versus pathogen evolution, we compared house finch responses to one of two MG isolates: the original VA1994 isolate and a more evolutionarily derived one, VA2013. To identify differential gene expression involved in initiation of the immune response to MG, we performed 3'-end transcriptomic sequencing (QuantSeq) of samples from the infection site, conjunctiva, collected 3-days post-infection. In response to MG, we observed an increase in general pro-inflammatory signalling, as well as T-cell activation and IL17 pathway differentiation, associated with a decrease in the IL12/IL23 pathway signalling. The immune response was stronger in response to the evolutionarily derived MG isolate compared to the original one, consistent with known increases in MG virulence over time. The host populations differed namely in pre-activation immune gene expression, suggesting population-specific adaptations. Compared to other populations, finches from Virginia, which have the longest co-evolutionary history with MG, showed significantly higher expression of anti-inflammatory genes and Th1 mediators. This may explain the evolution of disease tolerance to MG infection in VA birds. We also show a potential modulating role of BCL10, a positive B-and T-cell regulator activating the NFKB signalling. Our results illuminate potential mechanisms of house finch adaptation to MG-induced immunopathology, contributing to understanding of the host evolutionary responses to pathogen-driven shifts in immunityimmunopathology trade-offs.